EKSPLORASI ETNOMATEMATIKA PADA WISATA PANTAI PAPUMA JEMBER - Nurazizah, Siti; Nuryami (LPPM Institut Ahmad Dahlan Probolinggo, 2024)
Mathematics is a scientific discipline that deals with quantities, various forms, and concepts, not only having internal relations but also being connected to various fields, including culture. This research explores the concept of ethnomathematics at Papuma Beach, highlighting the interaction of mathematics with local culture. Ethnomathematics, the study of mathematical concepts in cultural contexts, is applied to the design and objects of Papuma Beach. Previously considered neutral, mathematics is now recognized as connected to culture and daily life. This study indicates that Papuma Beach is not just a tourist destination but also a reflection of mathematical values in community activities. The application of ethnomathematics in learning can enrich the material with cultural relevance for students. The focus of this research is the exploration of mathematical concepts in the design of Papuma Beach, with an emphasis on geometric patterns and mathematical proportions in coral rocks and surrounding objects. The research method used is a qualitative approach through ethnographic methods. Observation and documentation are the data collected in this research. Data analysis involves reduction, presentation, and interpretation of data. The results show that Papuma Beach, besides being a vacation spot, also depicts mathematical values in everyday life. This research provides a unique perspective on the interconnection between mathematics, culture, and architecture at Papuma Beach.. Keywords: Culture, Papuma Beach, Geometry